Identification and Expression Analysis of G Protein-Coupled Receptors in the Miridae Insect Apolygus lucorum - Gao, Han; Li, Yanxiao; Wang, Miao; Song, Xiaowen; Tang, Jing; Feng, Fan; Li, Bin (Frontiers in Endocrinology, 2021)
G protein-coupled receptors (GPCRs) are the largest and most versatile family of transmembrane receptors in the cell and they play a vital role in the regulation of multiple physiological processes. The family Miridae (Hemiptera: Heteroptera) is one of the most diverse families of insects. Until now, information on GPCRs has been lacking in Miridae. Apolygus lucorum, a representative species of the Miridae, is an omnivorous pest that occurs worldwide and is notorious for causing serious damage to various crops and substantial economic losses. By searching the genome, 133 GPCRs were identified in A. lucorum. Compared with other model insects, we have observed GPCR genes to be remarkably expanded in A. lucorum, especially focusing on biogenic amine receptors and neuropeptide receptors. Among these, there is a novel large clade duplicated from known FMRFamide receptors (FMRFaRs). Moreover, the temporal and spatial expression profiles of the 133 genes across developmental stages were determined by transcriptome analysis. Most GPCR genes showed a low expression level in the whole organism of A. lucorum. However, there were a few highly expressed GPCR genes. The highly expressed LW opsins in the head probably relate to nocturning of A. lucorum, and the expression of Cirl at different times and in different tissues indicated it may be involved in growth and development of A. lucorum. We also found C2 leucine-rich repeat-containing GPCRs (LGRs) were mainly distributed in Hemiptera and Phthiraptera among insects. Our study was the first investigation on GPCRs in A. lucorum and it provided a molecular target for the regulation and control of miridae pests.